Konsep Pendidikan Karakter dalam Islam (Studi Komparasi atas Pemikiran K.H. Hasyim Asy'ari dan Syeikh Az-Zarnuji): Concept of Character Education in Islam (Comparative Study of the Thought of K.H. Hasyim Asy'ari and Sheikh Az-Zarnuji) - Nur Anisa, Lina (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This article examines the thoughts of K.H. Hasyim Asy’ari and Syeikh Az-Zarnuji on character education and their relevance in the context of modern education. The primary focus of this study is to identify the fundamental values they taught and explore how these principles can be applied in today’s educational system. The research employs a literature review method, analyzing the key works of both scholars, namely Adab al-‘Alim wa al-Muta’allim by K.H. Hasyim Asy’ari and Ta’lim al-Muta’allim by Syeikh Az-Zarnuji. The findings reveal that, despite their different social and cultural backgrounds, both scholars emphasize the importance of morality, sincerity in seeking knowledge, and the teacher’s role in shaping students’ character. The implementation of these ideas in the national curriculum and pesantren-based education can serve as a solution to strengthening character education amid the challenges of globalization. Therefore, their teachings remain relevant in shaping a generation with integrity, high morality, and the ability to navigate societal changes while upholding strong Islamic values.